2018
DOI: 10.3390/polym10020211
|View full text |Cite
|
Sign up to set email alerts
|

α-Cyclodextrin and α-Cyclodextrin Polymers as Oxygen Nanocarriers to Limit Hypoxia/Reoxygenation Injury: Implications from an In Vitro Model

Abstract: Abstract:The incidence of heart failure (HF) is increasing worldwide and myocardial infarction (MI), which follows ischemia and reperfusion (I/R), is often at the basis of HF development. Nanocarriers are interesting particles for their potential application in cardiovascular disease. Impaired drug delivery in ischemic disease is challenging. Cyclodextrin nanosponges (NS) can be considered innovative tools for improving oxygen delivery in a controlled manner. This study has developed new α-cyclodextrin-based f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 37 publications
1
42
0
Order By: Relevance
“…It is widely acknowledged that H/R is a hazardous factor, resulting in myocardial apoptosis and necrosis, which are two key cellular events in AMI. 2,20 In the present study, our data supported that H/R induced myocardial cell injury, as evidenced by the repression of cell proliferation and the promotion of cell apoptosis, in accordance with previous studies. 25,26 Subsequently, we further explored the effect and underlying mechanism of ANRIL on AMI by H/Rinduced myocardial cells.…”
Section: Discussionsupporting
confidence: 93%
“…It is widely acknowledged that H/R is a hazardous factor, resulting in myocardial apoptosis and necrosis, which are two key cellular events in AMI. 2,20 In the present study, our data supported that H/R induced myocardial cell injury, as evidenced by the repression of cell proliferation and the promotion of cell apoptosis, in accordance with previous studies. 25,26 Subsequently, we further explored the effect and underlying mechanism of ANRIL on AMI by H/Rinduced myocardial cells.…”
Section: Discussionsupporting
confidence: 93%
“…The production of nanocarriers is one the most innovative and promising research fields in modern pharmaceutical technology: As a matter of fact, the use of nanoscale formulations can improve drug compatibility [1,2], provide more accurate diagnosis [3,4], reduce the risk of immune response [5,6], and achieve targeted drug delivery [7,8]. Despite the aforementioned scientific advancements, the market of nanoscale medical devices is still a niche one, not only because of regulatory issues, but also because of the difficulties encountered in producing nanocarriers at an industrial scale [9].…”
Section: Introductionmentioning
confidence: 99%
“…Various host molecules such as cyclodextrins (CD), urea, thiourea, cyclo-triphosphazines, pillar [6]arene, cucurbit [6]uril, and calix [4]arene have been identified as undergoing inclusion complexation with a range of guest molecules. Among these host molecules, cyclodextrins are well-known for their complexation capabilities with a variety of guest molecules.…”
mentioning
confidence: 99%
“…By complexation, the third and fourth articles in this Special Issue address these two major challenges in tissue regeneration [4,5]. By encapsulating oxygen into the cavities of α-CD and α-CD polymers, in vitro cell studies demonstrated a marked reduction in hypoxia-reoxygenation injury, leading to favorable cell growth and lowered cell mortality [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation